Morphological and Physiological Characteristics of Ebf2-EGFP-Expressing Cajal-Retzius Cells in Developing Mouse Neocortex. (11th October 2018) - Sun, Le; Chen, Ruiguo; Bai, Ye; Li, Jia; Wu, Qian; Shen, Qin; Wang, Xiaoqun
Abstract: Cajal-Retzius (CR) cells are one of the earliest populations of neurons in the cerebral cortex of rodents and primates, and they play a critical role in corticogenesis and cortical lamination during neocortical development. However, a comprehensive morphological and physiological profile of CR cells in the mouse neocortex has not yet been established. Here, we systematically investigated the dynamic development of CR cells in Tg(Ebf2-EGFP)58Gsat/Mmcd mice. The morphological complexity, membrane activities and presynaptic inputs of CR cells coordinately increase and reach a plateau at P5–P9 before regressing. Using 3D reconstruction, we delineated a parallel-stratification pattern of the axonal extension of CR cells. Furthermore, we found that the morphological structure and presynaptic inputs of CR cells were disturbed in Reelin-deficient mice. These findings confirm that CR cells undergo a transient maturation process in layer 1 before disappearing. Importantly, Reelin deficiency impairs the formation of synaptic connections onto CR cells. In conclusion, our results provide insights into the rapid maturation and axonal stratification of CR cells in layer 1. These findings suggest that both the electrophysiological activities and the morphology of CR cells provide vital guidance for the modulation of early circuits, in a Reelin-dependent manner.